2015
DOI: 10.1161/cir.0000000000000144
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Arrest and Cardiopulmonary Resuscitation Outcome Reports: Update of the Utstein Resuscitation Registry Templates for Out-of-Hospital Cardiac Arrest

Abstract: Utstein-style guidelines contribute to improved public health internationally by providing a structured framework with which to compare emergency medical services systems. Advances in resuscitation science, new insights into important predictors of outcome from out-of-hospital cardiac arrest, and lessons learned from methodological research prompted this review and update of the 2004 Utstein guidelines. Representatives of the International Liaison Committee on Resuscitation developed an updated Utstein reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
229
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 820 publications
(243 citation statements)
references
References 72 publications
3
229
0
11
Order By: Relevance
“…EMS response time is an important determinant of survival after an OHCA 16, 17, 18. Several recent studies of OHCA have reported a negative effect of increasing EMS response time on clinical outcomes, a finding consistent with our study 10, 19, 20, 21, 22, 23.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…EMS response time is an important determinant of survival after an OHCA 16, 17, 18. Several recent studies of OHCA have reported a negative effect of increasing EMS response time on clinical outcomes, a finding consistent with our study 10, 19, 20, 21, 22, 23.…”
Section: Discussionsupporting
confidence: 91%
“…Since 2005, with the cooperation of the physician in charge, EMS personnel at each center recorded data from patients with OHCA using an Utstein‐style template 16, 17. The data are transferred to local, individual fire stations and subsequently integrated into the registry system on the FDMA database server.…”
Section: Methodsmentioning
confidence: 99%
“…The study design requires that inferences based on outcomes must be made with caution and the relationships indicated between factors should be viewed as associations and not cause and effect. Notwithstanding, high data quality was pursued through prospective and uniform data collection through the CARES registry, following Utstein guidelines for reporting cardiac arrest 20. We included data from only selected counties.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study population included all out‐of‐hospital cardiac arrests from 16 counties in North Carolina, covering a total population of ≈3 million inhabitants (30% of the total state population) with demographics varying from urban to rural areas. Following the Utstein guidelines for reporting cardiac arrest, the study population included cases of cardiac arrest with presumed cardiac cause and ≥18 years of age during 2010–2014 and excluded cases witnessed by a 911 responder or with “do not resuscitate” orders 20. Because patient sex was the main interest in this study, we excluded cases with missing sex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation